Implementasi Sila Ketuhanan Yang Maha Esa Pancasila Dalam Pembentukan Karakter Siswa Di SMA Budisatrya Medan - Nur Hidayah Hasibuan; Muhammad Iraqi Fauzi; Tri Bayu Armanda; Mira Cahya; Dyna MT Pasaribu; Ramsul Nababan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the implementation of the First Principle of Pancasila at Budisatrya Medan High School in shaping student character. The research method used is qualitative with a descriptive approach. Data collection techniques were carried out by interviews with students and teachers. The research results show that the implementation of the First Principle of Pancasila at Budisatrya Medan High School is quite effective in shaping student character. This can be seen from students' habits of praying, participating in religious activities, and trying to act honestly, fairly, and responsibly. The school has also carried out various programs to implement the First Principle of Pancasila, such as express Islamic boarding schools, congregational prayers in prayer rooms, providing religious extracurricular activities, and providing prayer rooms for Muslim students.